2003
DOI: 10.1038/sj.ejcn.1601540
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between methylmalonic acid, homocysteine, vitamin B12 intake and status and socio-economic indices, in a subset of participants in the British National Diet and Nutrition Survey of people aged 65 y and over

Abstract: Objective: Assessment of functional vitamin B 12 status in a subset of the respondents in the British National Diet and Nutrition Survey of people aged 65 y and over. Setting: National Diet and Nutrition Survey: a British nationwide cross-sectional sample of people aged 65 y and over, living either in the community or in institutions such as nursing homes, during one calendar year spanning 1994 -1995. Methods: Methylmalonic acid (MMA) concentrations were measured in plasma samples from 313 subjects (ca 14% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…Further, serum concentrations of these metabolites are lowered with vitamin B 12 therapy even when serum concentrations of vitamin B 12 started within the 'normal' range (Henning et al, 2001). The prevalence of deficient serum vitamin B 12 (12%) in older New Zealanders is higher than that reported in the United States in people Z60 y (B5%) (Wright et al, 1998) but lower than that reported in the United Kingdom in people aged 465 y (20%) (Bates et al, 2003). The reasons for the differing rates of deficient serum vitamin B 12 concentrations among these countries are unclear because median dietary intakes of vitamin B 12 are similar.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Further, serum concentrations of these metabolites are lowered with vitamin B 12 therapy even when serum concentrations of vitamin B 12 started within the 'normal' range (Henning et al, 2001). The prevalence of deficient serum vitamin B 12 (12%) in older New Zealanders is higher than that reported in the United States in people Z60 y (B5%) (Wright et al, 1998) but lower than that reported in the United Kingdom in people aged 465 y (20%) (Bates et al, 2003). The reasons for the differing rates of deficient serum vitamin B 12 concentrations among these countries are unclear because median dietary intakes of vitamin B 12 are similar.…”
Section: Discussionmentioning
confidence: 95%
“…Estimates of the prevalence of low serum vitamin B 12 concentrations (o150 pmol/l) in older people range from 3 to 6% in the United States and 20% in the United Kingdom (Wright et al, 1998;Bates et al, 2003). In most cases, low serum vitamin B 12 concentrations in older people are not accompanied by megaloblastic anaemia.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, functional measures of status such as plasma or urinary methylmalonic acid, holotranscobalamin and homocysteine (tHcy) indicate a more widespread vitamin B 12 deficiency. Thus, a more detailed analysis of UK elderly subjects within NDNS has indicated that 46% of institutionalised elderly have elevated methylmalonic acid (106) . Importantly, several UK population studies of the elderly in the community have identified similar frequencies of elevated methylmalonic acid and have shown that low vitamin B 12 status, as indicated by elevated methylmalonic acid, low holotranscobalamin or elevated tHcys, is associated with cognitive decline (107)(108)(109) .…”
Section: Vitamin B 12mentioning
confidence: 99%
“…Estimates among the elderly vary widely; from 5% (based upon a low serum vitamin B 12 concentration) among institutionalized elderly adults in Germany, The Netherlands and Belgium (32) to 46% (based on multiple criteria including serum vitamin B 12 and methylmalonic acid (MMA)) among institutionalized elderly adults in the UK (33) . The impact on estimates of prevalence of using different criteria of deficiency can be illustrated by adapting data presented for a UK cohort of elderly adults (34) .…”
Section: Prevalencementioning
confidence: 99%